Video denoising algorithm based on improved dual-domain filtering and 3D block matching - Xiao, Jinsheng; Zou, Wentao; Zhang, Shangyue; Lei, Junfeng; Wang, Wen; Wang, Yuan-Fang (IET image processing, 2018)
This study introduces an algorithm for video denoising based on improved dual-domain filtering and 3D block matching. The wavelet thresholding based on 3D block matching is introduced to make full use of the correlation of video sequence in order to apply dual-domain filtering to the video. A layered approach is used that attempts denoising in both a base layer and a detail layer. The result of wavelet thresholding based on 3D block matching is used as a guide image to make the base layer smoother. Shrinkage of short-time Fourier transform coefficients further decreases the noise in the detail layer. Experimental results show that the authors’ algorithm generates a better base layer and detail layer than the traditional dual-domain filtering algorithms. The subjective and objective comparisons of different algorithms also prove that the proposed algorithm performs better for video denoising.